2011
DOI: 10.4028/www.scientific.net/amr.243-249.1156
|View full text |Cite
|
Sign up to set email alerts
|

Service Life Prediction Based on Carbonation Reliability Theory for Reinforced Concrete under Mechanical Load

Abstract: A carbonation model of reinforced concrete structures subjected to mechanical load based on experimental work is proposed in the paper. Correspondingly, a series of reliability analysis and service life prediction is carried out and reasonable results are acquired. Besides the effect of concrete cover, it indicates that mechanical load impacts the reliability and service life of the reinforced concrete structures significantly through example calculation. In the case of concrete cover of 40mm, the service life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Many factors affect the concrete carbonation: water–cement ratio [ 1 , 2 ], supplementary cementitious materials [ 1 , 3 , 4 , 5 , 6 , 7 , 8 ], CO 2 concentration [ 9 , 10 , 11 ], relative humidity [ 9 , 12 , 13 , 14 ], and applied load [ 8 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Much work based on the standard test methods and specifications has been carried out on concrete specimens in a load-free status without considering the effect of applied load.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many factors affect the concrete carbonation: water–cement ratio [ 1 , 2 ], supplementary cementitious materials [ 1 , 3 , 4 , 5 , 6 , 7 , 8 ], CO 2 concentration [ 9 , 10 , 11 ], relative humidity [ 9 , 12 , 13 , 14 ], and applied load [ 8 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Much work based on the standard test methods and specifications has been carried out on concrete specimens in a load-free status without considering the effect of applied load.…”
Section: Introductionmentioning
confidence: 99%
“…A series of attempts have been made to study concrete carbonation damage under stress. Wan et al [ 18 ] and Tang et al [ 19 ] reported that the carbonation rate rises and then falls with compressive stress. Han et al [ 20 ] found that tensile stress deepened the carbonation depth, and compressive stress restrained concrete carbonation.…”
Section: Introductionmentioning
confidence: 99%